ACTIVE INVOLVEMENT OF PARENTS AND TEACHERS AS AN EFFORT TO PREVENT BULLYING OF CHILDREN IN ELEMENTARY SCHOOLS - Prasetyowati, Irma; Umniyah, Zahratul; Rahman, Hermanto; Mulyo, Fiskan Adi Santro; Haryanik, Meilinda Alya’ Putri (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Bullying is still a critical problem in Indonesia, especially in schools, where many unreported cases are also found, which then have a broad impact on children's welfare. Therefore, this community service activity aims to increase the knowledge and understanding of the target audience regarding bullying incidents in children and prevent bullying from occurring early on. Methods: This community service utilized a participatory approach at Selolembu State Elementary School, Bondowoso (June–August 2023), involving school staff, parents, and students to prevent bullying. The stages included initial observations, problem mapping, participatory assistance via focus group discussions, workshops on bullying prevention and parenting, establishing anti-bullying student cadres, and ongoing evaluations to measure the program's effectiveness. Results: Parents and teachers are critical in preventing bullying at school. Teachers play a role in increasing awareness, providing character education, and monitoring the school environment to prevent bullying incidents. They also participate in the development of anti-bullying policies and reporting systems. Parents play an active role in monitoring children's behaviour at home, especially regarding the use of technology, as well as being involved in school activities and policy-making. Collaboration between teachers and parents is essential to create a school environment that is safe and free from bullying. Conclusion:  The conclusion from the implementation of this activity is the need to monitor and strengthen the commitments set by the target audience so that program sustainability can be maintained.